BUDAYA TELEVISI DI INDONESIA: Wacana dan Kepentingan Ideologis dari Dua Periode - Ikhwan Setiawan (Universitas Airlangga, 2015)
This article deals with the discussion of cultural discourses in Indonesian televisions, from the New Order until the Reformation period. Applying Foucauldian and Gramscian theory as the primary framework and media theory as the supporting framework in reading some discursive constructions in television programs, I argue that there is discursive transformation in cultural discourses from the two periods that intertwines with politico-ideological interest negotiated by the regimes; Soeharto’s leadership in the former and capitalist class of television industries in the later. By reading some dominant programs in general, I found two dominant cultural discourses. The first is modernity colored by some communal values—i.e. integrity and harmony—in the midst of the New Order period. By such construction, the regime may negotiate and secure its politico-ideological interest, particularly for succeeding the national development as a definite way to establish hegemonic power operation. The second is various cultural discourses—including traditional, religious, and metropolitan values—represented by private televisions as the reflection of freedom spirit in the midst of society which is incorporated by capitalist class. There is a transformation of cultural discourses marked by principle of flexibility in which some residual cultures articulated in modern atmosphere with newer-invested meanings. Such condition intertwines with the changing of the leading class formation in the midst of neoliberal system. The state regime still becomes the ruling class which controls political and administrative affairs, but the capitalist class takes the leading position which drives people’s imagination, orientation, and praxis.